China’s New Military Leaders: Civil-Military Relations in Xi Jinping Era - Char, James (2017)
The recently-concluded 19th Congress of the Chinese Communist Party has confirmed Xi Jinping’s dominance over the trident of party-state-military power. The downsizing of the Central Military Commission and its appointment of Xi’s favoured generals endorsed his status as China’s new strongman. Whether Xi can translate his huge clout into a fundamental transformation of the Chinese military remains to be seen.